Efficiency of Therapeutic Plasma-Exchange in Acute Interstitial Lung Disease, Associated With Polymyositis/Dermatomyositis Resistant to Glucocorticoids and Immunosuppressive Drugs: A Retrospective Study - Ning, Yaogui; Yang, Guomei; Sun, Yuechi; Chen, Shiju; Liu, Yuan; Shi, Guixiu (Frontiers in Medicine, 2019)
Interstitial lung disease (ILD) is a life-threating complication, commonly associated with polymyositis (PM) and dermatomyositis (DM). Owing to its resistance to conventional therapies, acute ILD associated with PM/DM leads to a high rate of mortality in patients. The efficacy of therapeutic plasma-exchange (TPE) as a PM/DM treatment to improve muscle involvement is controversial due to a lack of evidence. However, in some case reports, TPE has been effective in improving lung involvement. To evaluate the efficacy of this therapy, we retrospectively studied the treatment outcomes of TPE in 18 acute PM/DM-ILD patients who were resistant to conventional therapies. We also analyzed risk factors to predict unresponsiveness to TPE in these patients. Among 18 patients, 11 (61.1%) achieved satisfactory improvement after four or more rounds of TPE, whereas seven died due to respiratory failure. Subcutaneous/mediastinal emphysema and increased serum ferritin levels were shown to be poor prognostic factors of unresponsiveness to TPE in PM/DM patients. Our results indicate that TPE might be an alternative treatment for acute PM/DM-ILD patients resistant to conventional therapies, except for those with subcutaneous/mediastinal emphysema and high serum ferritin levels.